Development of Khutbah Books: Media for Increasing Student Soft Skills in PAI Courses at Universitas Nahdlatul Ulama Blitar - Abdurrachman Sidik; Siti Uswatun Kasanah; Zainal Rosyadi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2021)
The purpose of this study is to conduct a Khutbah book as a medium for improving student soft skills in PAI courses at Nahdlatul Ulama University Blitar. The focus of this research is the development of the Khutbah book as a medium for improving student soft skills with content according to updated scientific and social developments. Using the Research and Development method developed by Borg and Gall which includes preliminary studies, research planning, design development, product testing, revision of limited field test results, extensive product testing, revision of wider field test results, feasibility test, final revision of test results feasibility, dissemination and implementation of the final product. Data were collected from the assessment of two experts through the Expert validation sheet and 57 students respondents through a student respondent questionnaire. Data analysis used qualitative and quantitative approach techniques. Data in the form of suggestions and criticisms from experts/experts and students were analyzed with a qualitative approach, while data on the feasibility of the Khutbah book and opinions regarding the suitability of the book were processed using a quantitative descriptive approach. Data analysis that the Khutbah book needs to be arranged in accordance with scientific and social developments in society. The results showed that the Khutbah book was suitable for use in the development of student soft skills.